"Field Study" of the Aryan Movement: In-Class Film and Activity for the Qualitative Methods Course - Keys, Jennifer (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
"Allowed access to national gatherings of U.S. radical right groups including the KuKlux Klan and the Posse Comitatus, Blood In The Face straightforwardly presents theviews of people whose avowed goal is to forge a political union which will transformNorth America into one Aryan nation. Blatantly and without flinching, members of thesegroups describe their agenda of anti-Semitism, racism, and extreme nationalism. Theirheroes are Adolf Hitler and George Lincoln Rockwell, founder of the American NaziParty. Wedding ceremonies are performed at burning crosses. Their message is spreadthrough their own home video network." http://www.frif.com/cat97/a-e/blood_in.html